Gene therapy with VEGF 165 for angiogenesis in experimental acute myocardial infarction Terapia gênica com VEGF 165 para angiogênese no infarto agudo do miocárdio experimental - Roberto T. Sant'Anna (Brazilian Journal of Cardiovascular Surgery, 2003)
OBJECTIVE: Evaluate coronary angiogenic response to transmural injection of plasmid encoding VEGF 165 in acute myocardial infarction (AMI) zones in a canine model. METHODS: The heart of eleven dogs was exposed and AMI was induced by occlusion of the diagonal branch of anterior descending coronary artery. For each of 10 selected points in the infarction area and its peripheral zone injections of 1 ml of saline solution (control group: five dogs) or 1 ml of plasmid encoding VEGF 165 solution (200 µg/ml) (VEGF group: six dogs) were introduced. Tecnecium myocardial scintigraphy was performed immediately after animal recovery and 14 days later to evaluate the myocardial perfusion. The animals were sacrificed and the hearts were submitted to a histological study of the infarcted area, peripheral zone and normal posterior ventricular wall, to evaluate the number of arterioles and capillaries. RESULTS: Immediate modifications in myocardial perfusion found in scintigraphic studies were similar in both groups. In the second evaluation at 14 days, hypoperfusion of ischemic area had recovered by 70% to 90% when compared to the day of AMI. Histologic evaluation of the peripheral area of AMI indicated a larger number of vessels in the VEGF group when compared to controls (mean: 123.81 + 21.48 and 40 + 6.13, p < 0.01, respectively). This increase resulted mainly from an increase in the number of capillaries (97.5 + 16.04 in the VEGF group and 22.18 + 3,25 in control group, p < 0.01), as the number of arterioles did not increase significantly. In the VEGF group, a comparison in the number of vessels of the AMI peripheral area and normal myocardium revealed a non-significant increase of vessels in the ischemic area (123.81 + 21.48 and 95.14 + 41.19). CONCLUSION: An intramural injection of plasmid VEGF 165 resulted in a significant increase in the number of capillaries in the peripheral AMI area. This increase may have a beneficial effect in the reduction and recovery of the ischemic area secondary to AMI. OBJETIVO: Verificar a indução de angiogênese miocárdica pela injeção transmural de plasmídeo VEGF 165 (Genentech/ USA) em zonas do infarto agudo do miocárdio (IAM) de cães, mediante avaliação por cintilografia miocárdica e estudo histológico. MÉTODOS: Em onze cães anestesiados o coração foi abordado em toracotomia antero-lateral esquerda e produzido IAM pela ligadura simples de ramo diagonal da artéria coronária descendente anterior. Em cada de 10 pontos selecionados da área infartada e sua periferia foi realizada a injeção de um total de 1 ml de solução salina (grupo controle: cinco cães) ou de solução contendo plasmídeo VEGF 165 na concentração de 200 ug/ml (grupo tratado: seis cães). Os animais foram recuperados e realizada cintilografia miocárdica com Tecnécio imediatamente e 14 dias após IAM. Os animais foram sacrificados e o coração retirado para estudo histológico da área de infarto, de sua periferia e de área da parede ventricular posterior, visando contagem eletrônica de capilares e arteríolas. RESULTADOS: Cintilografia mostrou modificações na perfusão miocárdica comparáveis entre os grupos quanto ao estudo imediato e 15 dias após IAM, sendo que os dois grupos mostraram uma recuperação de 70 a 90 % da hipoperfusão demonstrada no 1o exame. O estudo histológico da área de transição do IAM revelou um maior número de vasos no grupo tratado em relação ao grupo controle (média de 123,81 + 21,48 e 40 + 6,13, respectivamente; p <0,01). Este crescimento do número de vasos é atribuível principalmente ao aumento do número de capilares (97,5 + 16,04 no grupo tratado e 22,18 + 3,25 no grupo controle, p < 0,01), sendo que em relação ao número de arteríolas o aumento não foi significativo (25,16 + 10,89 e 16,8 + 4,75; NS). A comparação entre a região de transição do IAM do grupo tratado e de área normal, revelou um maior número de vasos na região tratada, ainda que a diferença não fosse significativa (respectivamente 123,81 + 21,48 e 95,14 + 41,19, p > 0,05). CONCLUSÕES: Injeção transmural de plasmídeo VEGF 165 resultou em significativo aumento no número de capilares na zona de transição do IAM experimental. O aumento de capilares pela terapia gênica tem presumível efeito benéfico na redução e recuperação da área isquêmica.